Optimalisasi Pemanfaatan Zakat Profesi Kantor Kementerian Agama Kabupaten Kediri Di Sektor Pendidikan - Mukhsapak; Reza Ahmad Zahid (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
Zakat has great potential to be used to support development in the aspect of developing religious moral values through education. The Ministry of Religion of Kediri Regency seeks to apply Law number 23 of 2011 article 15 paragraph (1) in the context of implementing zakat management in order to improve education. In this study, the authors used descriptive qualitative research. The results of the study can be concluded, in channelling zakat for education in the Ministry of Religion Kediri is appropriate and refers to the distribution of zakat for the sabilillah class. Where all people who take the path of Allah, fight for His religion, both through seeking knowledge and who take up the sword, are equally entitled to receive Zakat. And the result, being able to help children who want to drop out of school because of their parents' unstable economy.